Application of the ‘Responsibility to Protect’ norm to the International Community’s Response to the Humanitarian Crises in Zimbabwe and Darfur - Spies, Yolanda Kemp (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2016.